2002
DOI: 10.1007/s00442-002-1044-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of competition: thermal inhibition of tree seedling growth by grass

Abstract: The relative importance of thermal interference and competition for below-ground resources in the inhibition of tree seedling growth by grass was determined under field conditions. Snow gum (Eucalyptus pauciflora) seedlings were grown in bare soil or soil covered with either live grass or straw. Covering soil with straw produced thermal conditions in soil and air that were indistinguishable from those associated with live grass. In contrast, seedlings grown in bare soil experienced more rapid increase in soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 23 publications
(31 reference statements)
2
38
1
Order By: Relevance
“…This thermal effect may be more beneficial to seedlings grown in bare soil than in the grass vegetation treatment, but we did not observe aerial phenology delay between both treatments nor differences in growth in 2001. These findings contrast with those obtained by Ball et al (2002) who reported, in Eucalyptus pauciflora seedlings, stress from temperature extremes induced by grass vegetation. The importance of these cold temperatures in tree growth and development could be species-dependant (Dang and Cheng 2004) as we know that pines exhibit ecophysiological adaptations to minimise the effect of frost and cold temperature (Rundel and Yoder 1998).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This thermal effect may be more beneficial to seedlings grown in bare soil than in the grass vegetation treatment, but we did not observe aerial phenology delay between both treatments nor differences in growth in 2001. These findings contrast with those obtained by Ball et al (2002) who reported, in Eucalyptus pauciflora seedlings, stress from temperature extremes induced by grass vegetation. The importance of these cold temperatures in tree growth and development could be species-dependant (Dang and Cheng 2004) as we know that pines exhibit ecophysiological adaptations to minimise the effect of frost and cold temperature (Rundel and Yoder 1998).…”
Section: Discussioncontrasting
confidence: 86%
“…In fertile grasslands characterised by a tall and dense grass canopy, competition for light is more conspicuous (Soussana and Lafarge 1998). Others have also suggested that extreme temperature fluctuations, aboveground and below-ground, induced by grass vegetation, may have or not dramatic consequences for seedlings survival and growth depending on the considered species and climate (Ball et al 1997(Ball et al , 2002Provendier and Balandier 2004). From these examples, we can conclude that in many cases exploitative grasses are probably unfavourable to tree establishment and growth, but the determinants need to be identified.…”
Section: Introductionmentioning
confidence: 95%
“…Plant cover alters microclimatic conditions in ways that can further influence nutrient availability (Ball et al 2002). It is well known that the experimental alteration of nutrient availability in a sward changes plant species composition and richness (Tilman 1984;Barnes et al 1987;Gough et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The only study that considered more than one species found similar responses (George and Brennan 2002). Ellis (1990) x Ellis et al (1985) x Chingaipe (1985) x Fagg (1988) x x x x Fagg (1988) x x x Postplanting weed control Ball et al (2002) x Dalton (1992) x x Fagg (1988) x x x Fagg (1988) x x x x Little and van den Berg (1999) x Soil cultivation Ellis (1990) x McKimm and Flinn (1979) x x Measki et al (1998) x Lacey et al (2001) x ? ?…”
Section: Growthmentioning
confidence: 97%